TESTS OF POLY ACRYLIC ACID (PPA) INHIBITOR ON BARIUM SULFATE SCALE INHIBITION EFFEICIENCY - Tjuwati Makmur (Scientific Contributions Oil and Gas, 2008)
Injection water (containing sulphate ion) is injected into reservoir (containing barium ion), mixture of incompatible water types results in barium sulphate scale occurrence.